Student Preferences in Using Affordable Learning Materials to Teach Research Methods Online - Grant, Phillip D; Pope, Elizabeth (International journal for the scholarship of teaching and learning, 2022)
This basic qualitative study assessed students’ perceptions of affordable learning materials in an asynchronous master’s level research methods course at a regional university. Students preferred instructor-created mini-lectures (45%) more than required readings (39%), supplementary items concerning a specific topic (7%), sample studies (5%), CITI training modules (3%), and continuing education materials (2%). We found that students tended to prefer material that offered foundational information about research methods. Students also preferred material that “translated” academic language. Students preferred materials that were compatible with their perceived learning style. Finally, students preferred materials that related research methods to their own professional practice.